Analisis Pengaruh Citra Merek dan Kepercayaan Konsumen terhadap Celebrity Endorsement pada Bm.studio Bali: Analysis of the Influence of Brand Image and Consumer Trust on Celebrity Endorsements at Bm.studio Bali - Yuandini, Kadek Diah (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This research aims to examine the influence of brand image and consumer trust on celebrity endorsements. The data collection method is carried out through questionnaires. The population of this research is BM Studio Bali Instagram followers, numbering around 11,000, with a sample of 100 respondents selected using the Slovin formula with a margin of error of 10%. The data obtained was then tested for validity, reliability and classical assumption tests, followed by multiple linear regression analysis and correlation analysis. The results of multiple regression tests show that brand image has a positive influence on celebrity endorsement, as well as consumer trust. The conclusion of this research is that brand image and consumer trust simultaneously have a significant influence on celebrity endorsement at BM Studio. Brand image has a positive and significant influence on celebrity endorsement at BM Studio, while consumer trust also has a partially positive and significant influence on celebrity endorsement at BM Studio.